Differential diagnosis of neonatal alloimmune thrombocytopenia: Type 2B von Willebrand disease. (17th November 2017) - Penel-Page, Mathilde; Meunier, Sandrine; Fretigny, Mathilde; Le Quellec, Sandra; Boisseau, Pierre; Vinciguerra, Christine; Ternisien, Catherine; Rugeri, Lucia
Abstract: At birth, severe thrombocytopenia without context of infection should mainly suggest neonatal alloimmune thrombocytopenia (NAIT), especially in case of a platelet count below 20 GL −1 . We report two cases of severe neonatal thrombocytopenia, first suspected as being NAIT. Both had a platelet count below 20 GL −1 with platelet clumps. The absence of alloantibodies and failure of platelet transfusion and intravenous immunoglobulins to improve the platelet count led to question the diagnosis and to evoke inherited bleeding disorders. Measurements of Von Willebrand factor (VWF) levels showed a marked reduction of VWF:RCo and a normal VWF:Ag, suggesting a type 2B Von Willebrand disease (VWD2B). Ristocetin-induced platelet aggregation could not be performed because of the very low platelet count. In the first case, after sequencing VWF exon 28, a heterozygous p.Leu1460Pro mutation was found consistent with VWD2B. In the second case, the genetic analysis of VWF exon 28 identified a homozygous mutation: p.Pro1337Leu confirming type VWD2B and also the p.Arg854Gln homozygous mutation in exon 20 confirming type 2N (ratio FVIII/VWF:Ag <0.5). The two cases underline that, even if NAIT remains the most common diagnosis in severe neonatal thrombocytopenia, it should be challenged in the absence of documented incompatibility, chronic evolution, or treatment failure. Diagnosis of VWD2B should be considered in early thrombocytopenia, even without familial history. In the cases presented, genotyping confirmed the subtype of VWD and helped to guide the therapeutic management of bleeding episodes.